Continuing Education in Plastic, Reconstructive and Aesthetic Surgery in Europe and its Relevance for Patient Safety - Giunta, Riccardo E. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2022)
Dear Readers,In this issue, the European Society of Plastic, Reconstructive and Aesthetic Surgery (ESPRAS) has dealt with the quality of continuing education in plastic surgery in Europe in the form of an “ESPRAS Survey”. An overview of the high quality criteria that are necessary in all countries in order to successfully complete specialist training in plastic and aesthetic surgery is summarised clearly and in detail. In Europe, as in Germany, specialist training generally includes training in all body regions, a training period of about 6 years, a rotation in intensive care units for the care of critically ill patients as well as surgical catalogues and specialist examinations.